2016
DOI: 10.1002/bies.201600019
|View full text |Cite
|
Sign up to set email alerts
|

Did sex chromosome turnover promote divergence of the major mammal groups?

Abstract: Comparative mapping and sequencing show that turnover of sex determining genes and chromosomes, and sex chromosome rearrangements, accompany speciation in many vertebrates. Here I review the evidence and propose that the evolution of therian mammals was precipitated by evolution of the male‐determining SRY gene, defining a novel XY sex chromosome pair, and interposing a reproductive barrier with the ancestral population of synapsid reptiles 190 million years ago (MYA). Divergence was reinforced by multiple tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 85 publications
(95 reference statements)
1
41
0
Order By: Relevance
“…In addition, comparative genomic studies of sterilizing and nonsterilizing mitochondrial genomes that co-occur in a given species have shown that sterilizing genomes exhibit a higher rate of evolution (Darracq et al 2010(Darracq et al , 2011. As dioecy and sex-chromosomes have been suggested to drive speciation rates (Käfer et al 2014;Graves 2016), gynodioecy could reveal itself to be another reproductive system that facilitates reproductive isolation and thus speciation in a very effective way, in a tempo faster than phenotypic diversification (Orr 1995), resulting in cryptic species. Therefore, we expect that the accumulation of mutations in the mitochondrial genome occurs independently in the two S. nutans lineages and would ultimately induce reproductive isolation through cytonuclear genetic incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comparative genomic studies of sterilizing and nonsterilizing mitochondrial genomes that co-occur in a given species have shown that sterilizing genomes exhibit a higher rate of evolution (Darracq et al 2010(Darracq et al , 2011. As dioecy and sex-chromosomes have been suggested to drive speciation rates (Käfer et al 2014;Graves 2016), gynodioecy could reveal itself to be another reproductive system that facilitates reproductive isolation and thus speciation in a very effective way, in a tempo faster than phenotypic diversification (Orr 1995), resulting in cryptic species. Therefore, we expect that the accumulation of mutations in the mitochondrial genome occurs independently in the two S. nutans lineages and would ultimately induce reproductive isolation through cytonuclear genetic incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Such fusions are easily recognizable because they cause an odd number of chromosomes in a diploid karyotype of one sex and might be implicated with speciation (e.g. [50, 52, 53]). In A. burtoni , males and females have the same karyotype of 2n = 40 ([12], personal communication with Cesar Martins) indicating that chromosome fusions were not causing the formation of neo-sex chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…First, rearrangements involving sex chromosomes may be implicated in driving divergence between populations in the same manner as other chromosomal rearrangements, as outlined above (reviewed in Connallon et al 2018). Second, sex chromosome turnover may cause imbalance in the sex determination process of hybrids, resulting in hybrid infertility and therefore increasing divergence between populations with different sex chromosome systems (Haldane 1922;Dobzhansky 1937;Graves 2016). For both of these reasons, sex chromosome turnover may be a particularly important driver of population divergence and speciation.…”
mentioning
confidence: 99%